2022
DOI: 10.1002/cam4.5439
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic on breast, colorectal, lung, and prostate cancer stage at diagnosis according to race

Abstract: Purpose To determine if the COVID‐19 pandemic has further exacerbated racial disparities in late‐stage presentation of breast, colorectal, lung, and prostate cancers. Methods We conducted a registry‐based retrospective study of patients with newly reported diagnoses of breast, colorectal, lung, and prostate cancers between March 2019–June 2019 (pre‐COVID‐19) and March 2020–June 2020 (early‐COVID‐19). We compared the volume of new diagnoses and stage at presentation acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…This study investigated the impact of COVID‐19 pandemic on diagnosis and treatment of cancers by considering other causes both before and during the corona were sustained. 16 , 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study investigated the impact of COVID‐19 pandemic on diagnosis and treatment of cancers by considering other causes both before and during the corona were sustained. 16 , 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…In another study by Maringe et al 15 This study investigated the impact of COVID-19 pandemic on diagnosis and treatment of cancers by considering other causes both before and during the corona were sustained. [16][17][18] In this study, the data was obtained only from patients in Iran, however, since there is a uniform cancer stage system across most coun- infections on head and neck cancer stage might be more challenging than other sites of cancers because it contains high concerns of the disease spread for both patients and healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The disease is now known to affect multiple organs and cause a wide range of symptoms, 3−5 including severe pneumonia, which can lead to the production of "white lungs". 6 Reports of persistent and prolonged effects after acute COVID-19 are also increasing. 7 Therefore, there is a critical need to develop a sensitive and efficient test method that can prevent and predict the occurrence and progression of similar diseases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has caused a global healthcare crisis and put significant strain on healthcare resources. , The disease is now known to affect multiple organs and cause a wide range of symptoms, including severe pneumonia, which can lead to the production of “white lungs” . Reports of persistent and prolonged effects after acute COVID-19 are also increasing .…”
Section: Introductionmentioning
confidence: 99%
“…45 Other studies in the US, South America, Europe, the Middle East, and Asia, obtained similar results. [12][13][14]30,43,[46][47][48][49] Studies showing no tumor shift, as displayed in the presented results, are scarce, 11,15 but may also have been underreported. Our study showed no difference in terms of frequency and modalities of breast reconstruction surgery in 2020 compared to 2019, unlike other studies that found less breast reconstruction surgeries post-pandemic, in consistence with scientific recommendations.…”
mentioning
confidence: 96%